Efikasi Herbisida Atrazin terhadap Gulma Umum pada Lahan Budidaya Tanaman Jagung (Zea mays L.) - Mustajab Mustajab; Dad R. J. Sembodo; Herawati Hamim (Jurnal Penelitian Pertanian Terapan, 2015)
The objective of this research was to know the efficacy of atrazine herbicide to control the common weed in maize (Zea mays L.) field and how was the phytotoxicity to maize (Zea mays L.) plant. The research was conducted in the Institute for Agricultural Technology assessment (BPTP), Natar Experimental Field, South Lampung regency with ultisol soil type and Weeds Laboratory Faculty of Agriculture, University of Lampung, from June to September 2013. The experiment was arranged in Completely Randomized Block Design (CRBD) with six treatments and four replications. The treatments are atrazine herbicide at 1.2, 1.6, 2.0, and 2.4 kg ha-1, mechanic weeding, and control. Homogeneity of variance was tested by Bartlett test and additivitty tested by Tukey's test, the comparison of mean were tested by Least Significant Difference (LSD) test at 5% level. The result showed that (1). Atrazine herbicide at 1.2 – 2.4 kg ha-1 could suppress total weed until 6 Week After Treatment (WAT). (2) Atrazine herbicide at 1.2–2.4 kg ha-1 could suppress broadleaves and grasses weed until 6 WAT. (3) Atrazine herbicide did not cause phytotoxicity symptoms to the maize (Zea mays L.).plant. Keywords: Weed, Efficacy, Atrazine, Maize